PENERAPAN ALIRAN PENDIDIKAN PROGERSIVISME PADA STRATEGI PEMBELAJARAN BAHASA INDONESIA SISWA KELAS X SMA NEGERI 1 NA IX-X - Nining Mindayani (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2019)
Abstract The flow of education Progressivism is a flow of modern educational philosophy that requires a change in the implementation of education to be more advanced. This flow of progressivism prioritizes the implementation of education in schools centered on children and makes educators only as facilitators, mentors, and directors to students. The objectives of this research are; 1) to find out whether the teacher's views on education are in accordance with the flow of progressivism, 2) to find out whether the teacher's role has been carried out in accordance with the flow of progressivism, 3) whether the teacher has designed a learning strategy in accordance with the flow of progressivism. The results of this study are; 1) The teacher is of the opinion that education is very important, because it changes a person's personality into a better person, changes his character attitude for the better and is useful for his present life and future life, 2) educators are only as facilitators who foster children and direct children to search for truth in a science. So the teacher's task is only to make how students get knowledge from the potential that exists within themselves, so that he can develop independently, 3) The strategy used by the teacher is learning independently. Students are expected to learn to find information by exploring the initial information provided by the teacher. Then the teacher is only tasked with supervising and monitoring how students dig up that information. The findings obtained by students will get an explanation by the teacher so students or students can better understand the findings they find. Keywords: Progressivism Flow, Learning Strategies, High School Students Grade X